Resistance Test on Aeromonas hydrophila Isolated from African Catfish (Clarias gariepinus) Against Some Antibiotics Groups (Indonesian Society for microbiology, 2017)
Aeromonas hydrophila is a type of bacteria causing Motile Aeromonads Septicemia (MAS) disease, which infects freshwater fish, including African catfish, and leads to death as well as huge losses to farmers. This research aims to determine the resistance status of various antibiotic classes in A. hydrophila bacteria isolated from African catfish. Bacterial isolates of A. hydrophila were taken from the liver and kidneys of infected African catfishes obtained from Parung, Bogor. Characterization of the bacteria was carried out based on colony morphology and biochemical properties. Meanwhile, bacterial resistance test was conducted using antibiotic disks with Kirby-Bauer method. Based on colony morphology and biochemical properties, the characterization results indicated that the bacterial isolates tested were A. hydrophila. Further examination of the antibiotic resistance test showed that the bacteria were resistant to penicillin antibiotics and macrolides. Future researches are expected to use molecular identification for A.hydrophila bacteria mutant to known the DNA base.Â